Assistive courseware for visually-impaired - Aziz, Nurulnadwan; Mohamad Roseli, Nur Hazwan; Abdul Mutalib, Ariffin (Springer Berlin Heidelberg, 2009)
Research in aiding disabled people with electronic applications should be one of the focuses in the area of human-computer interaction.The population of disabled is big and increasing, so they should be entertained well so that they will be potential resources to the nation.This paper discusses the Assistive Courseware (AC) in terms of how visually-impaired (VI) can make full use of them. It aims to propose guidelines for developing AC for VI people.In the introduction part, current issues regarding disabilities and the population is discussed.It also outlines the objectives of the paper.Next, the research methodology is outlined.There are three phases in which AC development is in the second phase which adapts the IntView courseware development methodology. The final part of the paper contains results of the test, which proposes basic guidelines for developing AC for VI.